THE ROLE OF GENDER IN ECOPRENEURSHIP: AN INVESTIGATION OF STARTUPS AT AN INCUBATION CENTER (Third Sector Social Economic Review, 2023)
Environmentally conscious entrepreneurship, also known as ecopreneurship, has gained attention for its potential to promote economic growth while addressing environmental concerns. This study examines the role of gender representation in ecopreneurship within the context of startup companies. While women are known to prioritize social and ecological factors in business management, limited research has explored their influence on startups. The study draws on social role theory and institutional theory to examine the relationship between gender representation among founders and the likelihood of startups adopting environmental orientation. In this regard, data from 131 startups within İTÜ Çekirdek incubation center were analyzed. The findings reveal that contrary to the hypothesis, there is no significant relationship between ventures that have women founders and the likelihood of these ventures being environmentally oriented. This result suggests that gender representation alone may not be a decisive factor in shaping the environmental focus of startups. Other factors, such as market conditions, regulatory frameworks, and business strategies, play significant roles in determining ecopreneurship. The study underscores the need for a nuanced understanding of how gender interacts with entrepreneurial decisions. It also points out that individual motivation for environmental entrepreneurship can vary widely, even among startups in the same ecosystem. The research can contribute to ongoing discussions about the multifaceted nature of ecopreneurship and offer future research directions in this field.
Keywords: Ecopreneurship; startups; women entrepreneurs; gender roles; institutional theory